Cancer literacy differences of basic knowledge, prevention, early detection, treatment and recovery: a cross-sectional study of urban and rural residents in Northeast China - Li, Mengdan; Ni, Ping; Zuo, Tingting; Liu, Yunyong; Zhu, Bo (Frontiers in Public Health, 2024)
Background Cancer literacy as a potential health intervention tool directly impacted the success of cancer prevention and treatment initiatives. This study aimed to evaluate the cancer literacy in Northeast China, and explore the factors contributing to urban–rural disparities. Methods A cross-sectional survey was conducted in 14 cities across Liaoning Province, China, from August to October 2021, using the multistage probability proportional to size sampling (PPS) method. The survey comprised 4,325 participants aged 15–69 and encompassed 37 core knowledge-based questions spanning five dimensions. Associations between sociodemographic factors and the cancer literacy rate were evaluated using chi-square tests and multivariate logistic regression model. Results The overall cancer literacy rate was 66.9% (95% CI: 65.6–68.2%). In the primary indicators, cancer literacy were highest in treatment (75.8, 95% CI: 74.2–77.4%) and early detection (68.2, 95% CI: 66.8–69.6%), followed by basic knowledge (67.2, 95% CI: 65.8–68.6%), recovery (62.6, 95% CI: 60.7–64.5%) and prevention (59.7, 95% CI: 58.2–61.3%). Regarding secondary indicators, the awareness rates regarding cancer-related risk factors (54.7, 95% CI: 52.8–56.5%) and early diagnosis of cancer (54.6, 95% CI: 52.7–56.6%) were notably inadequate. Rural participates exhibited lower cancer literacy across all dimensions compared to urban. Multi-factor analysis showed that factors such as advanced age, limited education or low household income were barriers to health literacy in rural areas. Conclusion Strengthening awareness concerning prevention and early detection, particularly among key populations, and bridging the urban–rural cancer literacy gap are imperative steps toward achieving the Healthy China 2030 target.